Accounting Rules and the Labor Market for Accountants - LE, ANTHONY (Journal of Accounting Research, 2026)
ABSTRACT In this study, I explore how accounting rules—in particular the restrictiveness of GAAP—have impacted the labor market for accountants. I find that when the rules become more restrictive, there are fewer students majoring in accounting and fewer accountants and auditors overall. The overall number of accounting positions that firms recruit for does not decrease when the rules become more restrictive; however, the nature of accountants' work changes. There is less focus on tasks such as applying judgment, thinking creatively, and thinking critically and more focus on determining compliance. Despite the decrease in accountants, earnings for accountants do not increase, and the wage distribution becomes more compressed. I supplement these analyses with a survey‐based field experiment and find that the salience of restrictiveness heightens students' views of accounting as a profession where they are unable to use creative and critical thinking. Overall, the findings suggest that restrictive regulation can shift the task content of occupations and reduce the pool of individuals interested in the profession.